2019
DOI: 10.1002/app.48340
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization kinetics of PLA/nanosized YVO4 composites as a novel nucleating agent

Abstract: The influence of nanosized YVO 4 particles as a novel and efficient nucleating agent on the nonisothermal crystallization behaviors of poly(lactic acid) (PLA) was studied. A modified Avrami model was utilized to describe the nonisothermal crystallization kinetics of pure PLA and PLA nanocomposites. The differential isoconversional Friedmann formula was employed to calculate the effective activation energies (E X(t) ) of nonisothermal crystallization from the glass state. The results showed that modified Avrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…The phenomenon was in line with the literature. [35] Furthermore, we could confirm from the obtained n values that nanosized TiO 2 particles had no influence on the nucleation mechanism of the PP matrix. A similar result has been reported for PP matrix with other inorganic nucleating agents.…”
Section: Modified Avrami Modelmentioning
confidence: 63%
See 4 more Smart Citations
“…The phenomenon was in line with the literature. [35] Furthermore, we could confirm from the obtained n values that nanosized TiO 2 particles had no influence on the nucleation mechanism of the PP matrix. A similar result has been reported for PP matrix with other inorganic nucleating agents.…”
Section: Modified Avrami Modelmentioning
confidence: 63%
“…In addition, it is worth mentioning that the value of E a is negative since the crystallization rate increases with the decrease of the crystallization temperature. El-Taweel et al [35] had reported that a large E a absolute favored the process due to the exothermic nature of the crystallization. As shown in Figure 7, the crystallization processes of PP/BF/nano-TiO 2 composites were a multistep processes and the E a values increased with increasing the X t .…”
Section: Non-isothermal Crystallization Activation Energy Of Pp/bf/nano-tio 2 Composites By the Friedman Methodsmentioning
confidence: 99%
See 3 more Smart Citations